High sensitivity pressure measurement using optical fibre sensors mounted on a composite diaphragm - James, Stephen W.; Aime, Laura; Kissinger, Thomas; Chehura, Edmon; Tatam, Ralph P. (Cranfield University, 2021)
Data underlying the work presented in the paper "High sensitivity pressure measurement using optical fibre sensors mounted on a composite diaphragm", published in Optics Express, 2020. Each zip file contains the data and a text file describing the contents. Full details are provided in the paper
Keywords: fibre bragg gratings'; 'interferometry'; 'fibre optic sensors'; 'fibre segment interferometry'; 'Pressure Sensing'; 'diaphragm'; 'Photonics; Optoelectronics and Optical Communications'; 'Aerodynamics (excl. Hypersonic Aerodynamics)'